A Novel Inulin-Mediated Ethanol Precipitation Method for Separating Endo-Inulinase From Inulinases for Inulooligosaccharides Production From Inulin - Li, Xin; Zhang, Qiannan; Wang, Wei; Yang, Shang-Tian (Frontiers in Bioengineering and Biotechnology, 2021)
Inulin is a kind of polysaccharide that can be obtained various biomass. Inulooligosaccharides (IOS), a kind of oligosaccharides that can be obtained from inulin by enzymatic hydrolysis using inulinases, have been regarded as the functional food ingredients. Commercially available inulinases produced by natural Aspergillus niger contained both endo- and exo-inulinase activities.For IOS production from inulin, it is desirable to use only endo-inulinase as exo-inulinase would produce mainly the monosacchairde fructose from inulin. In the present study, a simple inulin-mediated ethanol precipitation method was developed to separate endo- and exo-inulinases present in natural inulinases. IOS production from inulin using the enriched endo-inulinase was then optimized in process conditions including pH and temperature, achieving a high yield of ~94%. The resultant IOS products had a degree of polymerization ranging from 2 to 7. The study demonstrated a novel method for obtaining partially purified or enriched endo-inulinase for IOS production from inulin in an efficient process, which can be readily scaled up for industrial application.